Tropheryma whipplei in children with diarrhoea in rural Ghana. (January 2016) - Vinnemeier, C.D.; Klupp, E.M.; Krumkamp, R.; Rolling, T.; Fischer, N.; Owusu-Dabo, E.; Addo, M.M.; Adu-Sarkodie, Y.; Käsmaier, J.; Aepfelbacher, M.; Cramer, J.P.; May, J.; et al.
Abstract: Tropheryma whipplei has been hypothesized to be able to cause diarrhoea, but data from young children are scarce. In this hospital-based case–control study 534 stool samples of children aged between 2 months and 15 years from rural Ghana were analysed for the presence of T. whipplei . Overall stool prevalence of T. whipplei was high (27.5%). Although there was no difference in T. whipplei carriage overall between cases and controls, cases aged between 0 and 12 months carried T. whipplei in their stool twice as often as controls without diarrhoea. The results from this study may support the hypothesis that T. whipplei can cause diarrhoea in first-time infection.